Evaluate The Use Of The Independent Registration Tools Outpatient Patients Using The Hot-Fit Method At Roemani Muhammadiyah Hospital Semarang - Wariyanti, Astri Sri; Nugrahaini, Alfian Listya (Procedia of Engineering and Life Science, 2024)
In Indonesia, the implementation of electronic medical records will begin to be implemented in health service facilities in December 2023 [1]. The HOT Fit method is a complete model in the aspect of the assessment carried out and is most suitable to existing problems compared to other models, where this model places three important parts, namely Human, Organization and Technology [2]. The aim of this research is to find out how to evaluate the use of the Outpatient Self-Registration Platform using the HOT – Fit Method.The method used is qualitative research with data for January until May 2024. The research instrument uses observation guidelines and interviewand data collection method is by observation and interview. How to collect data by observation Data processing techniques include data reduction, data display and verification. The research results show that from the human aspect of system users, the self-registration platform was socialized at the beginning of the implementation of the new system for users in outpatient registration but there was no training, and users were not satisfied with the features in the self-registration platform. Organizational aspects, support and policies from management provide support in its implementation, but system monitoring and written policies regarding the implementation of independent registration platforms have not been carried out. In terms of system quality, the independent registration platform at Roemani Muhammadiyah Hospital Semarang ensures data security because each officer has a username and password. In terms of benefits, the self-registration platform at Roemani Muhammadiyah Hospital Semarang is useful for its use, namely helping and facilitating patient care, especially reducing patient backlogs.